ANALISA HUKUM PENERAPAN RESTORATIVE JUSTICE DALAM UPAYA MEREFORMASI SISTEM PERADILAN UMUM DI INDONESIA - Edi, Nurcahyo; Pieris, John; Nelson Simanjuntak (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research is aimed to 1) How is restorative justice being assessed in the public justice system in Indonesia? 2) How is the implementation of restorative justice in law enforcement agencies in reforming the public justice system in Indonesia being analyzed? This research uses descriptive analytical method of normative juridical law. The results of the research shows that restorative justice has normatively become a mechanism for resolving legal cases in the context of the criminal justice system with the main stakeholders in the Police, Prosecutor's Office and Court. The development of various legal institutions such as the Police, Prosecutor's Office, Court and other legal institutions in the process of investigation and inquiry, arrest, detention, prosecution, until examination in court. The police in the criminal justice system have issued the Indonesian National Police Regulation No. 8 of 2021 concerning Handling Criminal Offences Based on Restorative Justice, for the purpose of afdoening buiten process by considering: the subject, object, category, and threat of the criminal offence; the background of the criminal offence; the level of harm; the loss or consequences of the criminal offence; the cost and benefit of handling the case; restoration to its original state; and the existence of peace between the victim and the suspect.